International Trade and Risk Sharing in the Global Rice Market: The Impact of Foreign and Domestic Supply Shocks - Shikha Jha; Kensuke Kubo; Bharat Ramaswami (Asian Development Bank (ADB), 2013)
In recent years, rising food prices have returned as a concern for policy makers especially in developing countries. In this context, this paper examines how supply shocks, both domestic and foreign, have mattered to imports and consumption in the global rice market over 1960–2010. Such an investigation is important in assessing the role of trade in compensating for domestic shocks. If shortages lead countries to impose trade restrictions, then trade may not be allowed to play an important role in stabilizing consumption. The existing literature has highlighted the importance of these policy shocks in the world rice market and how they have worked to increase the volatility of prices and trade flows. Although trade cannot be expected to play a strong role when the major producing and consuming countries are simultaneously hit by negative yield shocks, such a scenario obtains in only 3% of cases. However, we also find that consumption fails to be stabilized even when domestic shocks are negative and foreign shocks are positive; but imports do peak. Thus, while trade does help in coping with domestic risks, it is unable to achieve full risk sharing. Therefore, no matter what are the foreign shocks, the principal concern is to stabilize consumption when hit by negative domestic yield shocks. The frequency of such shocks is about 12%. This brings into play domestic responses, and we find that domestic stocks have been important in stabilizing consumption. The reliance on domestic policies has in turn kept the rice market thin.
hdl:11540/2077
Keywords: F14; Q17; 330; food prices; risk sharing; rice market; international trade; supply shocks